Assessment of the Arsenic Removal From Water Using Lanthanum Ferrite - García, Fabiana Elena (2021)
The catalytic performance of a perovskite-type lanthanum ferrite LaFeO3 to remove arsenic from water has been investigates for the first time. LaFeO3 was prepared by citrate auto-combustion of dry gel obtained from a solution of the corresponding nitrates poured into citric acid solution. Kinetic studies were performed in the dark with As(V) and in the dark and under UV-C irradiation at pH 6–7 with As(III) (both 1 mg L−1), and As : Fe molar ratios (MR) of 1 : 10 and 1 : 100 using the LaFeO3 catalyst. As(V) was removed from solution after 60 min in the dark in 7 % and in 47 % for MR=1 : 10 and MR=1 : 100, respectively, indicating the importance of the amount of the iron material on the removal. Oxidation of As(III) in the dark was negligible after 60 min in contact with the solid sample, but complete removal of As(III) was observed within 60 min of irradiation at 254 nm, due to As(III) photooxidation to As(V) and to As(III) sorption to a minor extent. Morphological and microstructural studies of the catalyst complement the catalytic testing. This work demonstrates that LaFeO3 can be used for the removal of As(III) from highly arsenic contaminated water.